Effects of directors and officers insurance on earnings management strategies: Moderating role of restatement announcements - Meng-Chi Chueh; Shen-Ho Chang (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2022)
Purpose: The purpose of this study investigates the role of directors and officers (D&O) insurance and restatement announcements in earnings management strategies. Design/methodology/approach: Using data on Taiwan's capital market, we implement two-stage method regression to examine the effects of D&O insurance on the earnings management strategies of firms and the role of restatement announcements. Findings: The results reveal that managers prefer to adopt accrual earnings management when firms have purchased D&O insurance. Moreover, the results reveal that restatement announcements cause managers to switch their earnings management strategies from accrual to real earnings management when firms have purchased D&O insurance. Research limitations/implications: This study has following research limitations. (1) the Taiwanese government requires listed firms to purchase D&O insurance; thus, the results of our analysis cannot be generalized to the period following the imposition of this requirement. (2) In contrast to the United States or other countries with high levels of investor protection, Taiwan's capital market is still an emerging capital market. Originality/value: Our study support the moderating role of D&O insurance, which constrains managers from manipulating earnings through accrual earnings management; they also highlight the risk-taking role of D&O insurance when firms make restatement announcements.
Keywords: G22; G32; G38; 330; D&O insurance; Accrual earnings management; Real earnings management; Restatement Announcement